MANAGEMENT OF SCHOOL OPERATIONAL ASSISTANCE FUNDS IN AS-SABIRIN BUBAA PRIVATE IBTIDAIYAH MADRASA IN PAGUYAMAN PANTAI DISTRICT OF BOALEMO REGENCY - Rizal; wingki dama; Sukrianto (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The study aims to describe the management of BOS (School Operational Assistance) funds in fulfilling the operations of private Islamic schools as Sabirin Bubaa, Paguyaman Pantai sub-district, Boalemo regency. The method used in this research is descriptive research with a qualitative approach, through the techniques of interview, observation, and documentation. The informants in this study were the Head of Madrasah, Treasurer, and Honorary Teacher. The result of the study shows that: 1) The planning of BOS funds has not gone well, because in the preparation of the RKAM teachers and school committees are not involved. 2) The implementation of BOS funds are following technical guidelines, although every year the BOS fund budget increases/decreases. 3) In the form of reporting BOS funds have not gone well, because the Private Islamic School AsSabirinBubaa is required to use all-digital (EMIS Data) and experience unstable network problems. 4) The accountability of Islamic School BOS funds is evidenced by the preparation of a report, although in making the LPJ there is evidence of the purchase of goods and scattered receipts. And to minimize this problem, the school coordinates with the shop. Keywords: Management, BOS, and Operational.